Gambaran Asuhan Keperawatan Mahasiswa Tentang Atraumatic Care Pada Anak Sakit - Suryani Hartati; Rosa Melati (Nursing News : Jurnal Ilmiah Keperawatan, 2021)
Nursing care that focuses on preventing trauma to children and families has been included in the semester learning plan, but not all nursing care carried out by students applies atraumatic care when treating pediatric patients in the hospital, due to the difficulty in performing atraumatic care. The purpose of this study was to determine the description of student nursing care about atraumatic care in sick children. This research method is descriptive with a mixed approach between quantitative and qualitative. The design of this study used a purposive sampling approach, with a population of nursing students in the fifth semester consisting of 93 students who submitted reports, of which 71 did not apply atraumatic care to the implementation. Data collection techniques through the provision of demographic data questionnaires, and direct interviews submitted by students answered by reasoning that they were more focused on disease as much as 37.8%, there was no assessment format as much as 24.4%, forgot to take atraumatic care actions as much as 23.2%, less understand concepts and skills as much as 11%, fear of children crying as much as 1.2% and lack of confidence as much as 2.4%. The conclusion is that students are less competent in understanding concepts and skills due to the adaptation process from education to hospitals. To improve student competence, direct practice to the clinic is better than laboratory practice, it is recommended to add or modify learning methods about atraumatic care material for students